Media Pembelajaran Simulasi Kelistrikan Otomotif Berbasis Web pada Mata Pelajaran Praktik AC Mobil - Setiawan, Intoyo Budi; Soeryanto; Agung, Achmad Imam; Arizal, Heru (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
The study findings indicate that the developed media was rated as "highly feasible" by media and subject matter experts. Classroom implementation received a "very good" response from students, who found it easier to comprehend the material. Furthermore, student learning outcomes improved significantly, with 100% successfully completing the post-test. The N-gain test results categorized the effectiveness of the simulation-based learning media as "moderate." Thus, this media has proven to be an effective and safe tool for enhancing students' understanding of AC electrical systems.